Shampoo With Basic Ingredients Chamomile Flower Extract (Matricaria Chamomilla): Formulation and Evaluation of Preparations - Permadi, Adi; Maulida Firdaus , Stradivary; Aziz , Abdul; Fatwa Zufar, Ahmad (Indonesian Journal of Chemical Engineering, 2023)
Proper hair maintenance is a crucial component of one's daily beauty regimen. Shampoo, a commonly utilized hair care solution, has a chemical blend that effectively eliminates filth while also offering moisturization and safeguarding. The objective of this study is to create shampoo formulations and preparations with chamomile extract. The chamomile flower extract contains active chemicals, specifically 1,3,4-trihydroxyflavones called apigenin and apigenin 7-o-glucoside. These compounds have several beneficial effects such as enhancing hair brightness and shine, as well as possessing antibacterial, antifungal, hypoglycemic, and antioxidant qualities. Shampoo's chemical composition is determined by analyzing factors such as pH, foamability, homogeneity, total plate count, yeast mold count, and other similar parameters. Upon examination of these criteria, it is evident that the formulation and shampoo formulations successfully complied with the test requirements outlined in SNI 06-2692-1992.